The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11517-014-1186-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and precision of 3D wireless measurement of scapular kinematics

Abstract: To direct interventions aimed at improving scapular position and motion in shoulder pathologies, a clinically feasible, objective, sensitive and reliable assessment of scapular dyskinesis is needed. The aim of this study is to evaluate the intra- and inter-observer reliability and the precision of 3D scapula kinematics measurement using wireless sensors of an inertial and magnetic measurement system (IMMS). Scapular kinematics during humerus anteflexion and abduction of 20 subjects without shoulder pathologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 38 publications
(64 reference statements)
3
46
0
Order By: Relevance
“…However, when inspecting the magnitude of ST ROMs, one might question their validity. When comparing to literature, reported ST ROM seems underestimated for lateral rotation and overestimated for posterior tilting [5,6,16,[24][25][26]. Parel et al [14,15] and van den Noort et al [26] reported good validity results for inertial sensor-based ST joint motion during arm elevation tasks, when an YZX-sequence for ST joint angle calculation was used [14][15][16]26].…”
Section: Discussionmentioning
confidence: 80%
“…However, when inspecting the magnitude of ST ROMs, one might question their validity. When comparing to literature, reported ST ROM seems underestimated for lateral rotation and overestimated for posterior tilting [5,6,16,[24][25][26]. Parel et al [14,15] and van den Noort et al [26] reported good validity results for inertial sensor-based ST joint motion during arm elevation tasks, when an YZX-sequence for ST joint angle calculation was used [14][15][16]26].…”
Section: Discussionmentioning
confidence: 80%
“…The most frequent analysis were conducted respectively high to low, involving nine (Botter et al, 2013;C.-H. Chen et al, 2013;Hernoux & Christmann, 2015;Kortier., 2015;Ogris et al, 2012;Seaman et al, 2010;Valero et al, 2016;van den Noort et al, 2014;Vignais et al, 2013) focused on hand and arm, four studies (Kortier et al, 2015;Peppoloni et al, 2016;Vignais et al, 2013;W. Y. Wong & Wong, 2008b) analyzed the trunk , five papers (Kuster et al, 2016;Vignais et al, 2013;Valero et al, 2016;Qin et al, 2014;Peppoloni et al, 2016) analyzed the movement of neck and shoulder, three paper (Holte et al, 2012;Antonio Diego-Mas et al, 2014;Botter et al,2013), analyzed posture.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects sat in a chair that was located approximately 60 cm from a 14-in. LCD monitor, and they assumed a whole-body posture that was in line with the American Society of Hand Therapists guidelines: the upper arm was positioned vertically, the elbow was flexed at 90°, and the forearm and wrist were set in neutral positions [23] (Fig. 1a).…”
Section: Protocolmentioning
confidence: 99%